Scared stiff - Ryan, Annelise (Ryan, Annelise. Mattie Winston mystery., 2010)
Halloween night in Sorenson, Wisconsin, usually resembles any other small town: trick-or-treaters, costume parties, and lots of cheerfully scary decorations. But Deputy Coroner Mattie Winston is finding this year a little different, because among all the fake carnage is a very real, very dead body...When Mattie and her boss/best friend, Izzy, are called to the home of waitress and part-time model Shannon Tolliver, they find the ghoulish decorations just a bit too authentic. For among the fake blood and skeletons is the corpse of Shannon herself - and the evidence screams murder. Since the whole town knows Shannon recently had a very public argument with her estranged husband, Erik, he's suspect No. 1 for homicide detective Steve Hurley. Tall, dark, and blissfully blue-eyed detective Steve Hurley, that is...But Mattie happens to know Erik truly loved his wife, and is simply incapable of the brutal act - even though he owns the exact same calibre handgun as the murder weapon...Determined to unearth the truth - and maybe spend a little quality time with Detective Hunky - Mattie puts her scalpel-sharp medical skills to work, and digs a little deeper. What she uncovers is stranger than anyone could have imagined...It seems Shannon's murder is just the tip of a very fatal iceberg. Now, in order to solve a case that's getting more dangerous by the minute - and to save Erik from the slammer - Mattie will have to risk everything to catch a killer who's capable of doing anything once he's cornered. And this time, it's not just Mattie's life that's on the line...